Analysis of Students' Needs and Characteristics to Develop Multiplication Domino-Card Learning Media Assisted by Articulate Storyline 3 - Yudhistira, Rendy Prima; Somakim, Somakim; Safitri, Erna Retna (Papanda Publisher, 2025)
Learning multiplication remains a challenge for many grade V students, particularly in memorizing multiplication facts and applying them in problem-solving. This condition underscores the need for more engaging, interactive, and learning-oriented media that align with students' learning styles and characteristics. Digital media has great potential to increase engagement and understanding of concepts. This study aims to analyze the learning needs and characteristics of students as the basis for developing domino-card multiplication learning media assisted by Articulate Storyline 3. The study used a quantitative descriptive design involving 130 students from three elementary schools in Musi Banyuasin Regency, South Sumatra. Data was collected through learning needs questionnaires, student characteristics questionnaires, and classroom observations, and then analyzed using descriptive statistics. The results showed that students have a high need for interactive media, with 79.6% liking digital, visual, and game-based media, as well as a high level of learning motivation (77.8%). Learning difficulties fall into the medium category (64.6%), particularly related to memorization and applying multiplication. Most students exhibit a visual-kinesthetic learning tendency, which corresponds to manipulative activities, animations, and interactive feedback. These findings suggest that the development of Articulate Storyline 3-assisted multiplication domino-card media is highly relevant, as it effectively addresses students' learning needs and supports increased engagement and conceptual understanding in the context of 21st-century learning.